PHLPP2 stabilization by p27 mediates its inhibition of bladder cancer invasion by promoting autophagic degradation of MMP2 protein. Issue 43 (25th October 2018) - Peng, Minggang; Wang, Jingjing; Zhang, Dongyun; Jin, Honglei; Li, Jingxia; Wu, Xue-Ru; Huang, Chuanshu
Abstract Pleckstrin homology domain leucine-rich repeat protein phosphatase 2 (PHLPP2) is a tumor suppressor that catalyzes the de-phosphorylation of the AGC kinases, while p27 acts as a tumor suppressor that regulates cell cycle, apoptosis, and cell motility. Our previous studies have identified that PHLPP2 participates in inhibition of transformation of human bronchial epithelial cells following lung carcinogen B[a]P/B[a]PDE exposure. However, nothing was known about the association of p27 with regulation of PHLPP2 expression and the role of PHLPP2 in bladder cancer (BC) invasion. In our current studies, we demonstrated that PHLPP2 inhibited BC invasion through promoting MMP2 degradation via p62-mediated autophagy; and p27 expression was able to stabilize PHLPP2 protein by inhibiting protein degradation of Hsp90, which could directly bind to PHLPP2 and protect it from degradation. More in-depth studies discovered that stabilization of Hsp90 by p27 was mediated by calpain1 proteolysis system, whereas p27 inhibited calpain1 gene transcription by attenuating Jak1/Stat1 cascade in human invasive BC cells. Collectively, we for the first time revealed PHLPP2 downregulation in BCs and its participating in promotion of BC invasion, as well as novel role of p27 and mechanisms underlying its regulation of PHLPP2 protein degradation through Hsp90-dependent manner. Our findings improve our understanding of p27 and PHLPP2 roles and their crosstalk in regulation of BC invasion, which further contributes to improve the current strategy for invasive bladder cancer therapy.